Superior cardiovascular protection with GLP-1 RAs over SGLT2 inhibitors in DM and HFpEF: A propensity score matching study. - Allen Cheng-Wei Li; Yang-Chi Lin; Jing-Yang Huang; Lung-Ching Chen; Su-Kiat Chua (PLoS ONE)
Background Heart failure with preserved ejection fraction (HFpEF) and diabetes mellitus (DM) are interrelated conditions associated with high morbidity and mortality. This study compared the cardiovascular protective effects of glucagon-like peptide-1 receptor agonists (GLP-1 RAs) versus sodium-glucose cotransporter-2 (SGLT2) inhibitors in this population. Methods This retrospective cohort study used data from the TriNetX database. It included 2,177 matched pairs of patients with HFpEF and DM treated with either GLP-1 RAs or SGLT2 inhibitors. Outcomes assessed over three years were a composite of all-cause mortality and progression to systolic heart failure, acute myocardial infarction, or stroke. Results GLP-1 RAs significantly reduced the risk of composite outcomes at one year (Hazard Ratio, HR 0.784; 95% CI, 0.658-0.934), two years (HR 0.813; 95% CI, 0.702-0.941), and three years (HR 0.825; 95% CI, 0.717-0.950). Specifically, GLP-1 RAs showed significantly reduced risks of progression to systolic heart failure (HR 0.60) and stroke (HR 0.75) compared to SGLT2 inhibitors. These protective effects were most pronounced in the first year and showed a slightly diminishing trend. While not statistically significant, GLP-1 RAs also exhibited a trend towards fewer myocardial infarctions (HR 0.83) and lower mortality rates (HR 0.83) than SGLT2 inhibitors. Subgroup analyses revealed more significant benefits in patients aged ≥60, women, Caucasians, those without moderate-to-severe chronic kidney disease or chronic ischemic heart disease, and those with better-controlled DM. Conclusions Among HFpEF patients with DM, GLP-1 RAs demonstrated superior cardiovascular protective effects compared with SGLT2 inhibitors over a 3-year follow-up period. Further randomized trials are required to confirm these findings.